2021
DOI: 10.3389/fnut.2021.746453
|View full text |Cite
|
Sign up to set email alerts
|

US Older Adults That Consume Avocado or Guacamole Have Better Cognition Than Non-consumers: National Health and Nutrition Examination Survey 2011–2014

Abstract: Purpose: The goal of this study is to examine how avocado relates to cognitive function among older adults.Methods: A total of 2,886 National Health and Nutrition Examination Survey 2011–2014 participants aged 60 or older met the eligibility criteria and were included of our cross-sectional study. Participants were binarily classified as avocado consumers (i.e., reported consuming any avocado/guacamole in either 24-h dietary recalls) or non-consumers. Cognitive performance was evaluated with: Consortium to Est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Similar findings were observed in an analysis of NHANES 2011-2014 participants aged 60 or older comparing avocado consumers to non-consumers. Specifically, avocado consumers had significantly higher z-scores for Consortium to Establish a Registry for Alzheimer's disease-immediate and delayed recall, and global cognition score, respectively (all p < 0.05 in adjusted models) [33]. More extensive and more prolonged trials are warranted to confirm these findings.…”
Section: Cognitive Functionmentioning
confidence: 89%
See 3 more Smart Citations
“…Similar findings were observed in an analysis of NHANES 2011-2014 participants aged 60 or older comparing avocado consumers to non-consumers. Specifically, avocado consumers had significantly higher z-scores for Consortium to Establish a Registry for Alzheimer's disease-immediate and delayed recall, and global cognition score, respectively (all p < 0.05 in adjusted models) [33]. More extensive and more prolonged trials are warranted to confirm these findings.…”
Section: Cognitive Functionmentioning
confidence: 89%
“…This study presents the first comprehensive review of Hass avocado clinical trials, observational studies, and biological mechanisms. We found that the Hass avocado has four major health benefits (Figure 17): (1) cardiovascular health [12][13][14][15][16][17][18][19][20][21][22]; (2), weight control [23][24][25][26][27][28][29][30]; (3) cognitive health [18,31,33]; and (4) colonic microbiota health [26,34]. We also found that four nutritional features were primarily responsible for all the major avocado health benefits: (1) high unsaturated to saturated fat ratio [7]; (2) viscous and prebiotic fiber [2,7]; (3) a relatively low energy density of 1.6 kcal/g [7]; and (4) high carotenoid bioavailability [35,36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its consumption is increasing signi cantly worldwide and it provides a lipid pro le almost identical to olive oil (21). Cheng et al (22) reported that American seniors who consumed avocado had improved cognitive performance than non-consumers.…”
Section: Introductionmentioning
confidence: 99%